(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
With a high percentage of Syrian refugees population in Jordan aged 18 - 35 years, the number of refugees that are willing to access the job market is very high. Therefore, many organizations try to make these refugees qualified by enrolling them within many educational and training programs in order to enhance their skills, thus make them able to find jobs. However, with the presence of many challenges that are facing Syrian youths in accessing the tertiary education system in Jordan, many organizations that offered scholarships at the tertiary education level couldn’t achieve the highest possible number of beneficiaries. Accordingly, this study aims to highlight the obstacles and inappropriate practices of many tertiary education initiatives that led to a low number of beneficiaries, in order to overcome repeating such practices in the future.